Enhancing accuracy and efficiency in upper extremity disability assessments: development and testing of a desktop application - Emre Ozmen; Gamze Gül Güleç; Hazal İzol Özmen; Melih Civan; Esra Circi; Serdar Yuksel; Alican Baris (Acta Orthopaedica et Traumatologica Turcica)
Objective: This study aimed to validate a software application (app) developed by the authors to streamline and enhance the accuracy of disability assessments, specifically for musculoskeletal system disabilities in the upper extremities.